Fecal Microbiota Transplantation in Neurological Disorders - Vendrik, Karuna E. W.; Ooijevaar, Rogier E.; de Jong, Pieter R. C.; Laman, Jon D.; van Oosten, Bob W.; van Hilten, Jacobus J.; Ducarmon, Quinten R.; Keller, Josbert J.; Kuijper, Eduard J.; Contarino, Maria Fiorella (Frontiers in Cellular and Infection Microbiology, 2020)
Background Several studies suggested an important role of the gut microbiota in the pathophysiology of neurological disorders, implying that alteration of the gut microbiota might serve as a treatment strategy. Fecal microbiota transplantation (FMT) is currently the most effective gut microbiota intervention and an accepted treatment for recurrent Clostridioioides difficile infections. To evaluate indications of FMT for patients with neurological disorders, we summarized the available literature on FMT. In addition, we provide suggestions for future directions. Methods In July 2019, five main databases were searched for studies and case descriptions on FMT in neurological disorders in humans or animal models. In addition, the ClinicalTrials.gov website was consulted for registered planned and ongoing trials. Results Of 541 identified studies, 34 were included in the analysis. Clinical trials with FMT have been performed in patients with autism spectrum disorder and showed beneficial effects on neurological symptoms. For multiple sclerosis and Parkinson’s disease, several animal studies suggested a positive effect of FMT, supported by some case reports in humans. For epilepsy, Tourette syndrome, and diabetic neuropathy some studies suggested a beneficial effect of FMT, but evidence was restricted to case reports and limited numbers of animal studies. For stroke, Alzheimer’s disease and Guillain-Barré syndrome only studies with animal models were identified. These studies suggested a potential beneficial effect of healthy donor FMT. In contrast, one study with an animal model for stroke showed an increased mortality after FMT. For Guillain-Barré only one study was identified. Whether the positive findings from animal studies can be confirmed in the treatment of human diseases awaits to be seen. Several trials with FMT as treatment of the above mentioned neurological disorders are planned or ongoing, as well as for amyotrophic lateral sclerosis. Conclusions Preliminary literature suggests that FMT may be a promising treatment option for several neurological disorders. However, available evidence is still scanty and some contrasting results were observed. Limited studies in humans have been performed or are ongoing, while for some disorders only animal experiments have been conducted. Large double-blinded randomized controlled trials are needed to further elucidate the effect of FMT in neurological disorders.